Pengaruh Diferensiasi Produk, Promosi Media Sosial Dan Kualitas Pelayanan Terhadap Minat Pembelian di Tea Break Sambi Kediri - Lestari, Afrilia Luluk; Kurniawan, Brahma Wahyu; Harianto, Kukuh (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the influence of product differentiation, social media promotion, and service quality on consumer purchase intention at Tea Break Sambi Kediri. The research employed an associative quantitative approach using a survey method with questionnaires distributed to 88 respondents selected through an accidental sampling technique. Data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis with SPSS version 25. The results revealed that both partially and simultaneously, product differentiation, social media promotion, and service quality have a positive and significant effect on purchase intention. Social media promotion is the most dominant variable influencing consumer buying interest, followed by service quality and product differentiation. These findings highlight the importance of creative digital promotion strategies and high service quality in enhancing consumer attraction and loyalty. This research provides practical implications for business owners in designing digital-based marketing strategies and academic contributions to the development of consumer behavior and marketing strategy literature within modern beverage SMEs.